Fatigue damage mechanism of titanium in vacuum and in air - Zahari, Nur Ismarrubie; Yussof, Hanafiah; Sugano, M. (Elsevier, 2012)
The fatigue damage of titanium has been studied on thin plate specimens subjected to alternating plane bending in two different environments: in vacuum (1.3 x 10-3 Pa) and in air. Fatigue properties of titanium were better in vacuum than in air. Fatigue damage was distinguished between the testing atmospheres. In vacuum, homogeneous fatigue slip bands formed on the {10 1 0} planes. Slip band microcracks were formed at the junction of intersecting slip bands developed on the {10 1 0} planes, remarkably. Fatigue behavior of titanium in vacuum was attributed to the higher slip activity at crack tip. However, in air fatigue damage was characterized by course slip bands and mechanical twins. Fatigue cracks in both atmospheres were propagated in transgranular mode in different manner: in vacuum, fatigue crack propagated along and across slip bands, but in air, fatigue crack mostly propagated in zigzag pattern.